Identification of candidate lethal haplotypes and recombination events in Nellore cattle - Schmidt, Patrícia Iana [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
With genomic data, lethal recessives may be discovered from haplotypes that are common in the population but are never homozygous in live animals. In addition, it also allows the characterization of patterns and rates of recombination that are important for the understanding of genetic diversity throughout the genome. The objectives of the present study were to identify lethal haplotypes, based on expected population frequencies and to build a recombination map for identify the hotspots regions for the understanding of genetic diversity of this Nellore cattle population. Pedigree information comprised 2,688,124 animals and the conflict.f90 software was used to correct Mendelian errors and fill missing SNP using parental genotypes. A total of 4,447 Nellore animals were genotyped with a high-density panel (777,962 SNP markers) and 4,041 with a panel containing 74,677 markers. Map locations are from the ARS-UCD1.2 Bos taurus genome assembly. The haplotypes were constructed using the sliding windows method implemented in findhap.f90 software v3. Expected numbers of homozygous individuals were calculated through two methods: Simple - assuming random mating and using the number of individuals genotyped divided by 4 and multiplied by the square of the carrier frequency; and Mating - using the actual mating pattern for calculating the number of carrier service sire × carrier maternal grandsire matings divided by 4. Recombination rates were measured by an indirect method, extracting progeny-sire pairs from pedigree of Nellore cattle. Both, sire and offspring were genotyped and phased in order to infer about recombination events for a paternal meiosis. Hotspot regions were defined as SNP intervals with recombination rate > 2.5 standard deviations above the mean. Twenty-six haplotypes had high expected frequency but no homozygotes observed. Two haplotypes on chromosome 1:56,408,787-56,947,331 and on 21:22,003,502- 22,770,526 overlaps with previously known defects: Deficiency of Uridine Monophosphate Synthase and Brachyspina syndrome, respectively. Furthermore, the candidate lethal haplotypes on chromosome 7:52,418,587-53,136,816 and on chromosome 12:27,930,543-28,993,509 match with potential signatures of selection found previously in a similar population of Nellore cattle. For the functional analyses, we used SIFT scores to classify mutations as deleterious or tolerant. We found 55 candidate genes responsible for harboring the deleterious mutations and 11 genes with tolerant mutations. We extracted 21,391 crossover events and 659 paternal meiosis with an average number of crossovers per meiosis of 32.4 for Nellore males. There were found 520 hotspots regions, especially in chromosomes 1, 6 and 11, with the highest recombination rates. We have found 52 candidate genes underlying hotspot regions and associated GO terms related pathways. Some pathways as Lysine degradation, Pyruvate metabolism, Viral myocarditis, Basal transcription factors and GO terms related to transcription and translation processes, were found. The detection of lethal haplotypes, as well as the characterization of recombination events in a population, provide important information regarding genetic diversity throughout the genome for a further improvement of genetic gain.

Com dados genômicos,alelos recessivos letais podem ser descobertos a partir de haplótipos comuns na população, mas que nunca são homozigotos em animais vivos; além disso, informações genômicas também permitem a caracterização de padrões e taxas de recombinação que são importantes para a compreensão da diversidade genética em todo o genoma. Os objetivos do presente estudo foram identificar haplótipos letais, com base nas frequências populacionais esperadas, e construir um mapa de recombinação para identificar as regiões de hotspots para o entendimento da diversidade genética dessa população de gado Nelore. As informações genealógicas compreenderam 2.688.124 animais e o software conflict.f90 foi usado para corrigir erros mendelianos e imputar SNP’s ausentes usando genótipos parentais. Um total de 4.447 animais Nelore foram genotipados com um painel de alta densidade (777.962 marcadores SNP) e 4.041 com um painel contendo 74.677 marcadores. As coordenadas genômicas dos marcadores foram baseadas na montagem do genoma Bos taurus ARS-UCD1.2. Os haplótipos foram construídos usando o método de janelas deslizantes implementado no software findhap.f90 v3. O número esperado de indivíduos homozigotos foi calculado por meio de dois métodos: Simples - assumindo acasalamento aleatório e usando o número de indivíduos genotipados dividido por 4 e multiplicado pelo quadrado da frequência de portadores; e Acasalamento - utilizou o padrão de acasalamento real, considerando o número de acasalamentos do touro portador e do avô materno portador dividido por 4. As taxas de recombinação foram medidas por um método indireto, extraindo pares de progênie-pai do pedigree de bovinos Nelore. Ambos, pai e filhos, estavam genotipados e foram faseados para inferir eventos de recombinação para uma meiose paterna. As regiões de hotspots foram definidas como intervalos SNP com taxa de recombinação > 2,5 desvios padrão acima da média. Vinte e seis haplótipos apresentaram alta frequência esperada, mas nenhum homozigoto foi observado. Dois haplótipos no cromossomo 1:56408787-56947331 e em 21:22003502-22770526 se sobrepõem a defeitos previamente conhecidos, Deficiência de Uridina Monofosfato Sintetase e síndrome de Braquispina, respectivamente. Além disso, os candidatos haplótipos letais no cromossomo 7:52418587-53136816 e no cromossomo 12:27930543-28993509 correspondem a possíveis assinaturas de seleção encontradas anteriormente em uma população semelhante de bovinos Nelore. Para as análises funcionais, usamos escores SIFT para classificar as mutações como deletérias ou tolerantes. Encontramos 55 genes candidatos responsáveis por abrigar as possíveis mutações deletérias e 11 genes com mutações tolerantes. Extraímos 21.391 eventos de recombinação e 659 meioses paternas com um número médio de recombinações por meiose de 32,4 para machos Nelore. Foram encontradas 520 regiões de hotspots, principalmente nos cromossomos 1, 6 e 11, com maiores taxas de recombinação. Encontramos 52 genes candidatos subjacentes às regiões de hotspot e às vias relacionadas aos termos do GO associadas. Foram encontradas algumas vias como degradação da lisina, metabolismo do piruvato, miocardite viral, fatores de transcrição basal e termos de GO relacionados aos processos de transcrição e tradução. A detecção de haplótipos letais, bem como a caracterização de eventos de recombinação em uma ii população, podem ajudar a fornecer um conhecimento importante sobre a diversidade genética em todo o genoma para uma melhoria adicional do ganho genético.
Identificação de candidatos a haplótipos letais e eventos de recombinação em bovinos Nelore
Keywords: beef cattle; expected frequencies; haplotype phasing; homozygous individuals; paternal meiosis